2022
DOI: 10.3389/fimmu.2022.1024224
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune function during antineoplastic treatment is associated with 12-months survival in non-small cell lung cancer

Abstract: IntroductionThe immune system has proven to be a key player in the progression as well as containment of cancer with new treatment strategies based on immunotherapy targeting this interaction. Assessing immune function could reveal critical information about the immune response to therapeutic interventions, revealing predictive biomarkers for tailored care and precision medicine.MethodsWe investigated immune function in 37 patients with inoperable non-small cell lung cancer (NSCLC) undergoing treatment with P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(63 reference statements)
2
2
0
Order By: Relevance
“…This suggests that the increase in exhausted CD8+T lymphocytes in the BLI microenvironment may be closely related to the occurrence and progression of tumors. Our study found that NSCLC patients with concurrent BLI had better ORR and PFS after immunotherapy, consistent with previous studies (Cortellini et al, 2021a;Ryssel et al, 2022;Zhang et al, (2022)). The mechanism for this phenomenon may be that the characteristic tumor micro-environment of BLI is more suitable for PD-1/PD-L1 pathway inhibitors to work, thereby reversing T lymphocyte exhaustion in tumor tissues, restoring T lymphocyte activity, and better exerting anti-tumor effects.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the increase in exhausted CD8+T lymphocytes in the BLI microenvironment may be closely related to the occurrence and progression of tumors. Our study found that NSCLC patients with concurrent BLI had better ORR and PFS after immunotherapy, consistent with previous studies (Cortellini et al, 2021a;Ryssel et al, 2022;Zhang et al, (2022)). The mechanism for this phenomenon may be that the characteristic tumor micro-environment of BLI is more suitable for PD-1/PD-L1 pathway inhibitors to work, thereby reversing T lymphocyte exhaustion in tumor tissues, restoring T lymphocyte activity, and better exerting anti-tumor effects.…”
Section: Discussionsupporting
confidence: 93%
“…However, the sample size was too small to draw firm conclusions. It has previously been described that high ex vivo unstimulated cytokine release and low stimulated cytokine release may reflect exhaustion [14]. Thus, our data indicate that the immune system in CF might be exhausted or impaired after long-term persistent infection and inflammation [24], similar to what is seen in other types of inflammatory diseases [25].…”
Section: Cross-sectional Studysupporting
confidence: 79%
“…This might explain why studies of the CF immune response have found varying and at times inconsistent tendencies [9,12]. A new standardized immune assay (TruCulture -Myriad RBM, Austin, TX, US) has been developed and tested as a predictive and diagnostic tool to link systemic immune responses to clinical parameters in several clinical cohorts, including people undergoing surgery, people with cancer and people with neuroborreliosis [13][14][15][16]. TruCulture estimates unstimulated and stimulated cytokine release to TLR agonists in whole blood using test tubes containing standardized concentrations of different agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Combining whole blood stimulation with longitudinal sampling of patients has been used to monitor changes in responsiveness over time with regard to disease progression and treatment‐induced effects. For example, longitudinal sampling before and during treatment was performed to study innate immune function during different cancer treatments [63] and combinational antiretroviral therapy in HIV [64]. Further, longitudinally sampling COVID‐19 patients from admission to the hospital until dismissal (or death) revealed that lower release of IL‐1β upon LPS as well as IL‐12 and IL‐17A upon R848 stimulation at admission were associated with more severe disease at peak severity [65].…”
Section: Clinical Applications Of Whole Blood Stimulationmentioning
confidence: 99%